2019
DOI: 10.3390/plants8110500
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Plants Used by the Hmong in Thailand

Abstract: Exotic species are an integral part of the plants used by many ethnic groups, but they usually receive little attention and have been considered alien to the ethnobotanical data. Here, we analyze the plants used by Thai Hmong refugees that are not native to their current habitats in Thailand. We attempt to understand the sources of this knowledge. Do people maintain the original traditional knowledge related to exotic species when they migrate to a new region, or does new knowledge originate from acculturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Recent archeological, genetic, and historical evidence has further revealed that HM groups might originate from the Neolithic Daxi groups (~ 5000 to 3300 BCE) in the middle reaches of the Yangtze River [ 14 – 17 ] and migrated westward and southward into the Yungui Plateau due to climate changes and warfare. Historic documents suggested that the migrations and admixture of ancient source populations facilitated the formation of the present-day distributions of HM groups in Southeast Asia (mainly in Laos and Vietnam), Europe, the USA, and Australia during the Ming and Qing dynasties [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent archeological, genetic, and historical evidence has further revealed that HM groups might originate from the Neolithic Daxi groups (~ 5000 to 3300 BCE) in the middle reaches of the Yangtze River [ 14 – 17 ] and migrated westward and southward into the Yungui Plateau due to climate changes and warfare. Historic documents suggested that the migrations and admixture of ancient source populations facilitated the formation of the present-day distributions of HM groups in Southeast Asia (mainly in Laos and Vietnam), Europe, the USA, and Australia during the Ming and Qing dynasties [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many exotic species are appreciated by locals and incorporated through cultivation, gathering or purchase, thus enriching subsistence practices (Hurrell and Delucchi 2013;Medeiros 2013). The use of exotic species has been highlighted in several parts of the world as a local solution to diverse needs (Santos et al 2014;Nguanchoo et al 2019). With regard to medicinal (Bennett and Prance 2000;Medeiros et al 2017;Palmer 2004) and firewood (Doumecq 2019; Jiménez-Escobar and Martínez 2019) use, it has been pointed out that these plants are readily available, fast growing, and more tolerant to environmental disturbance than native species (Bennett and Prance 2000;Medeiros et al 2017;Palmer 2004).…”
Section: Introductionmentioning
confidence: 99%
“…But current research revealed that such exotic plant species are now a component of materia medica, playing an important role in the provision of primary health care to local communities in Zimbabwe. This is not surprising as previous research showed that in Bangladesh (Rahman & Roy 2014), Brazil (Alencar et al 2010(Alencar et al , 2014, Hawaii (Palmer 2004), India (Singh 2016), Kenya (Njoroge et al 2004), South Africa Semenya & Maroyi 2018), South America (Bennett & Prance 2000) and Thailand (Nguanchoo et al 2019) exotic plant species are receiving attention as components of traditional pharmacopoeia. Chinemana et al 1985, Gelfand et al 1985, Ndamba et al 1994, Mavi 1996, Chigora et al 2007 ).…”
Section: Medicinal Plant Diversitymentioning
confidence: 87%